Critical Analysis of the Concessions Renewal Regime of Public Telecommunications Services in Peruvian Legislation - Rivadeneyra Sánchez, Juan (2015)
The following article conveys a critical revision of the concessions renewal regimen as a matter of public telecommunication services of the Peruvian normative. For that, the author will focus on analyze the existing renewal forms of telecommunication in the Peruvian legislation, as well as the principles that rule the renewal processes of the telecommunication concessions. In addition, the author offers a new perspective about the authorities that are able to perform the process mentioned before, to finally show us the probability to reform the used methodology of the expiration dates of concessions based on certain principles,and bestow a modification proposal.